Adipokine RBP4 drives ovarian cancer cell migration - Yanyan Wang; Yilin Wang; Zhenyu Zhang (BMC, 2018)
Abstract Background Obesity has been linked to several types of cancers including ovarian cancer. Retinol binding protein 4 (RBP4) is an adipokine that drives the development of hyperinsulinemia and type II diabetes in obesity patients and animals. Previously, we have identified RBP4 as a serum marker for ovarian cancer. Here we further explored the consequence of RBP4 upregulation in ovarian cancer cells and its molecular mechanism. Results Our results show that RBP4 is overexpressed in ovarian cancer cells to the same extent as in adipose tissues. The overexpression of RBP4 in ovarian cancer cells promotes cancer cell migration and proliferation. At molecular level, cancer progression factors MMP2 and MMP9 are induced in response to RBP4 overexpression. We further investigated which signaling pathways are utilized by RBP4 to activate ovarian cancer cell migration. We found RhoA/Rock1 pathway is turned on and CyclinD1 is upregulated in RBP4 overexpressed cells. Inhibition of RhoA/Rock1 pathway reduces the RBP4-induced MMP2 and MMP9 expression. The RBP4 action is depend on its associated ligand vitamin A/retinol acid (RA) and possibly involves similar pathways as for conferring insulin resistance. Moreover, we show that knockdown of RBP4 significantly reduce cancer cell migration and proliferation as well as expressions of oncogenic factors. Conclusions Our results indicated that RBP4 can drive ovarian cancer cell migration and proliferation via RhoA/Rock1 and ERK pathway. It suggests that RBP4 act as a oncogene in ovarian cancer cells. Thus, RBP4 could be a molecular bridge between obesity and cancers and a potential target for treating obese cancer patients.